Glioma Biopsy Based on Hybrid Dual Time-Point FET-PET/MRI—A Proof of Concept Study - Furtak, Jacek; Rakowska, Józefina; Szylberg, Tadeusz; Harat, Marek; Małkowski, Bogdan; Harat, Maciej (Frontiers in Neurology, 2021)
Neuroimaging based on O-[2-(18F)fluoroethyl]-l-tyrosine (FET)-PET provides additional information on tumor grade and extent compared with MRI. Dynamic PET for biopsy target selection further improves results but is often clinically impractical. Static FET-PET performed at two time-points may be a good compromise, but data on this approach are limited. The aim of this study was to compare the histology of lesions obtained from two challenging glioma patients with targets selected based on hybrid dual time-point FET-PET/MRI. Five neuronavigated tumor biopsies were performed in two difficult cases of suspected glioma. Lesions with (T1-CE) and without contrast enhancement (T1 and T2-FLAIR) on MRI were selected. Dual time-point FET-PET imaging was performed 5–15 min (PET10) and 45–60 min (PET60) after radionuclide injection. The most informative FET-PET/MRI images were coregistered with MRI in time of biopsy planning. Five biopsy targets (three from high uptake and two from moderate uptake FET areas) thought to represent the most malignant sites and tumor extent were selected. Histopathological findings were compared with FET-PET and MRI images. Increased FET uptake in the area of non-CE locations on MRI correlated well with high-grade gliomas localized as far as 3 cm from T1-CE foci. Selecting a target in the motor cortex based on FET kinetics defined by dual time-point PET resulted in a grade IV diagnosis after previous negative biopsies based on MRI. An additional grade III diagnosis was obtained from an area of glioma infiltration with moderate FET uptake (between 1 and 1.25 SUV). These findings seem to show that dual time-point FET-PET-based biopsies can provide additional and clinically useful information for glioma diagnosis. Selection of targets based on dual time-point images may be useful for determining the most malignant tumor areas and may therefore be useful for resection and radiotherapy planning.